Platinum Group Elements in Ireland and Northern Ireland: a regional survey of Palaeogene magmatism - Morrison, Anna (Trinity College Dublin. School of Natural Sciences. Discipline of Geology, 2025)
Platinum Group Elements (PGE) play an essential role in green technologies, which are vital to achieving the Green Transition. They are currently classed as 'Critical Raw Materials' due to concerns over the security of their continued supply. Therefore, innovative research is required to identify new deposits and fertile areas, strengthening Europe's endogenous supply of PGE. Palaeogene igneous intrusions in the United Kingdom and Ireland have been identified as prospective areas for Ni-Cu-PGE exploration within Europe. Mafic Irish intrusions have been subject to PGE exploration since the ~1980s, but the fertility of the mantle feeding volcanism has not been directly verified. Their prospectivity is largely based on extrapolations from genetically related Scottish intrusions within the British and Irish Palaeogene Igneous Province (BIPIP). This project will place the first direct constraints on PGE enrichment in the lithospheric mantle beneath Palaeogene mafic and ultramafic intrusions in Northern Ireland and Ireland. A key component of the study is the extension and refinement of digital maps of regional Palaeogene dyke swarms, which aids understanding of conduit networks and mineralisation potential. The results of this study will contribute to the understanding of mantle processes during Palaeogene North Atlantic rifting and produce a comprehensive, open-access geochemical data set of PGE abundances in Northern Irish and Irish mafic rocks. Integration of this dataset with other deposits within the North Atlantic Igneous Province (NAIP) will help to de-risk future Ni-Cu-PGE exploration efforts. Initial findings confirm elevated PGE abundances (>MORB) and variable sulphide saturation histories, reflecting complex mantle processes within the proto-Icelandic plume. Variable Pt/Pd ratios provides evidence of the Northern Irish and Irish sector of the BIPIP as a transitional zone within the NAIP, reflecting changing geodynamic environments and plume conditions within a brief period. Our data also suggest the transitional geochemical signature within the BIPIP may be related to the cumulative effects of an evolving plume environment and proximity of melt generation to sub-continental lithospheric mantle. Extended dyke mapping enhanced understanding of the origins of radial swarms, with potential onshore and offshore origins in central igneous complexes. This study presents a foundation for future PGE exploration in Northern Ireland and Ireland and contributes valuable data towards understanding plume dynamics and prospective mineralising zones.
APPROVED
Keywords: Icelandic plume; Platinum Group Elements; Dykes; North Atlantic Igneous Province; British and Irish Palaeogene Igneous Province